2023
DOI: 10.3390/vaccines11020400
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses to HBV Vaccine in People Living with HIV (PLWHs) Who Achieved Successful Treatment: A Prospective Cohort Study

Abstract: Background: Understanding immune responses after HBV vaccination is important to prevent HBV infection in PLWH and to achieve successful treatment. Methods: Thirty-two PLWHs with CD4+ cell count > 350 cells/µL and HIV RNA < 200 copies/mL were vaccinated with 20 µg of HBV vaccine at weeks 0, 4, and 24 in this prospective study. We measured total HIV DNA levels, HBsAb titers and HBsAg-specific T-cell responses during follow-up time. Results: All patients achieved protective HBsAb titer after immunization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Although these data are not statistically significant, post-vaccination serological surveillance of people with these characteristics could be effective in controlling infection, pending a large-scale study to assess the impact of these factors. In addition, administering a booster dose or restarting the vaccination schedule could result in seroprotection, as has been reported in some studies [31].…”
Section: Discussionmentioning
confidence: 80%
“…Although these data are not statistically significant, post-vaccination serological surveillance of people with these characteristics could be effective in controlling infection, pending a large-scale study to assess the impact of these factors. In addition, administering a booster dose or restarting the vaccination schedule could result in seroprotection, as has been reported in some studies [31].…”
Section: Discussionmentioning
confidence: 80%
“…Recent studies have shown improvements in the effectiveness of the HBV vaccine in PLWH, particularly with seroconversion rates [ 89 , 90 , 91 ]. In Uganda, to assess the efficacy of HBV vaccines in PLWH, a cohort of 132 participants received both the base dose of the vaccine and the 1-month dose, and 127 received the 6-month dose.…”
Section: Hepatitis B Virus Vaccinationmentioning
confidence: 99%